2010
DOI: 10.1002/yea.1805
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemical and genetic approach to inhibit proteolysis by the proteasome

Abstract: Regulated protein destruction by the proteasome is crucial for the maintenance of normal cellular homeostasis. Much of our understanding of proteasome function stems from the use of drugs that inhibit its activity. Curiously, despite the importance of proteasomal proteolysis, previous studies have found that proliferation of the yeast Saccharomyces cerevisiae is relatively resistant to the effects of proteasome inhibitors such as MG132, even in the presence of mutations that increase inhibitor levels in cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…Support for APIS comes from genetic and biochemical evidence tying 19S base components to transcriptional activation domains (1,2), and from results of chromatin immunoprecipitation (ChIP) experiments showing that 19S base proteins are recruited to activated genes separately from 20S core components (1, 3, 4). These observations, however, are countered by reports that the proteolytic activity of the proteasome is important for transcriptional activation in yeast (5,6) and for repression of cryptic transcription in mammalian cells (7), and by the finding that 20S proteins also associate with active chromatin by ChIP, albeit with different temporal and spatial distributions than 19S proteins (1,8). Disparate observations on the involvement of 19S versus 26S proteasomes in transcription make it difficult to arrive at a unified view of how proteasome components interact with chromatin.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Support for APIS comes from genetic and biochemical evidence tying 19S base components to transcriptional activation domains (1,2), and from results of chromatin immunoprecipitation (ChIP) experiments showing that 19S base proteins are recruited to activated genes separately from 20S core components (1, 3, 4). These observations, however, are countered by reports that the proteolytic activity of the proteasome is important for transcriptional activation in yeast (5,6) and for repression of cryptic transcription in mammalian cells (7), and by the finding that 20S proteins also associate with active chromatin by ChIP, albeit with different temporal and spatial distributions than 19S proteins (1,8). Disparate observations on the involvement of 19S versus 26S proteasomes in transcription make it difficult to arrive at a unified view of how proteasome components interact with chromatin.…”
mentioning
confidence: 67%
“…1A), but whether 20S function is required for this process is controversial. Recently, we learned that the proteasome inhibitor MG132 is only partially effective in yeast because the tryptic-and caspase-like sites of the proteasome compensate for chemical inhibition of the chymotryptic site by MG132 (6). We therefore used a chemical-genetic strategy in which MG132 is combined with inactivating point mutations in the tryptic-(PUP1) and caspase-(PRE3) like sites to effect rapid and comprehensive inhibition of proteasome function (6, 13) (Fig.…”
Section: S and 20s Function Is Required For Full Activation Of Gal mentioning
confidence: 99%
“…To determine whether the proteasome was similarly required for Yap1 degradation, a cycloheximide chase experiment was carried out in the presence or absence of the proteasome inhibitor MG132. These experiments were performed in a strain lacking the Pdr5 ABC transporter protein as this genetic background has been found to facilitate use of MG132, likely through increasing the uptake of this drug (29). MG132 was added to one culture prior to beginning the cycloheximide chase assay.…”
Section: Rate Of Yap1 Proteolysismentioning
confidence: 99%
“…Cell pellets were stored at Ϫ80°C until lysis. To analyze the effect of combining proteasome mutations with chemical inhibition, 5-ml overnight cultures of PUP1PRE3pdr5⌬ and pup1pre3pdr5⌬ cells (obtained as a gift from the William Tansey laboratory at Vanderbilt University) (48) were prepared in YPAD (YPD with 0.002% adenine hemisulfate (Sigma, catalog number A9126)) and used to inoculate 30 ml of YPAD with or without 50 M MG132. The cells were cultured for 8 (to 0.6 -0.8 A 600 ) or 24 h (to Ͼ5 A 600 ) before centrifugation at 2,000 ϫ g for 5 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…6A). Recent studies have shown that although the inhibition of proteasome activity by MG132 targets mainly the chymotryptic activity of the proteasome the tryptic and caspase-like activities imparted by the Pup1 and Pre3 proteases are still present (48). Therefore, we treated pup1pre3pdr5⌬ S. cerevisiae with MG132 to see whether there was an increase in isoaspartyl damage.…”
Section: The Proteasome and Autophagy Pathways Do Not Controlmentioning
confidence: 99%